Comparing cardiology curricula: Europe vs. USA - Brilliant, Justin; Sahiti, Floran; Mages, Christine (European heart journal, 2025)
The global challenge to decrease the burden of cardiovascular disease has led to a critical examination of how we train future cardiologists. As the field evolves, there's a growing recognition that future doctors need comprehensive training to address the complex challenges ahead. However, significant differences persist in cardiology curricula across the Atlantic, reflecting varied approaches to medical education and healthcare systems.
Online veröffentlicht: 2. April 2025
Gesehen am 22.10.2025